2016
DOI: 10.2355/isijinternational.isijint-2015-648
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Borate Fusion Pre-treatment for ICP-AES Determination of Tungsten in High-speed Steel

Abstract: This paper suggests a rapid decomposition and dissolution method for stable solution preparation in inductively coupled plasma atomic emission spectrometry when tungsten in a highspeed steel is quantified. The steel sample was decomposed with a mixture of hydrofluoric and nitric acid, and then the resulting solution was fused with lithium tetraborate. The vitrified borate was able to dissolve in nitric acid containing tartaric acid to prepare the final sample solutions. This pre-treatment method has a superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Our previous paper has described an analysis of highspeed steel in which lithium borate fusion is carried out to prepare a nitric-acid solution in inductively coupled plasmaatomic emission spectrometry (ICP-AES). 2) The prepared solution for a high-speed steel sample had an analytical stability without tungsten precipitation. This paper sug-gests a new method for the sample preparation, based on a solidified glass body fused with lithium tetraborate, in the quantification of vanadium by flame AAS.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous paper has described an analysis of highspeed steel in which lithium borate fusion is carried out to prepare a nitric-acid solution in inductively coupled plasmaatomic emission spectrometry (ICP-AES). 2) The prepared solution for a high-speed steel sample had an analytical stability without tungsten precipitation. This paper sug-gests a new method for the sample preparation, based on a solidified glass body fused with lithium tetraborate, in the quantification of vanadium by flame AAS.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to digest a tool steel sample without remaining a residue and precipitating no tungsten hydrate. 1) For example, an acid mixture containing hydrochloric and nitric acids, 2) which easily digests a stainless steel sample, cannot completely decompose metal carbides and oxides (e.g., aluminum, calcium, and chromium 3) ) in a steel sample. Digestion of such carbides and oxides should be conducted by fusion procedures with potassium disulfate 4) and sodium carbonate.…”
Section: Introductionmentioning
confidence: 99%
“…Digestion of such carbides and oxides should be conducted by fusion procedures with potassium disulfate 4) and sodium carbonate. 5) Authors were previously suggested lithium tetraborate fusion procedures for a high-speed tool steel sample on ICP-AES 1) and X-ray fluorescence 6,7) analyses. Although these methods were successfully employed to determine alloyed elements, they cannot be applied for sulfur quantification because of the loss of sulfur during its fusion process.…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative analysis of high‐speed steel, which is a kind of high‐alloyed steel designed for cutting tools or heat jigs, is normally employed by inductively coupled plasma‐atomic emission spectrometry (ICP‐AES) . This ICP‐AES procedure, which always needs a pretreatment of samples using acid decomposition, is tedious and time‐consuming.…”
Section: Introductionmentioning
confidence: 99%